Etymology and Etiologic Tales of Tribes of Wayanad - V.Menon, Indu (School of Social Sciences, 2015)
The district Wayanad of Kerala state, India have the largest tribal population in Kerala with 8 scheduled tribes including Adiyan, Paniyan, Mullukkurman, Kurichyan, Vettakkuruman Wayanad Kadar, Kattuniakkan and Thachaanadan Mooppan. These communities have a number of symbolic oral narratives of how their community emerged, how they got their particular name, how the world began and how the people of their community first came in to inhabit in the world. These kinds of creation myths, founding myths, cosmogony myths and oral etiologic tales commonly develop in oral tradition and it has multiple versions in different areas. This paper explores the oral tales of the creation of each community and the origin of the name of the community This paper aims to provide an analytical comparison between oral traditions of different communities regarding the origin of their communities name the etymology of their community name.